2010
DOI: 10.3766/jaaa.21.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long Compression Release Times: Speech Understanding, Real-World Preferences, and Association with Cognitive Ability

Abstract: The relationship between cognitive abilities and performance with short and long release time processing was supported and further elucidated in this research. In addition, release time was seen to be a salient variable in subjective performance with amplification in daily life. Accurate prospective prescription of release time has the potential to make a material contribution to successful amplification provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
2
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 38 publications
5
54
2
2
Order By: Relevance
“…Lunner (2003) also suggested that it is important to note that the hearing aid processing may in itself be cognitively demanding. This is in agreement with the results reported by Gatehouse et al (2006) and Cox and Xu (2010) who showed that listeners with greater cognitive skills were more likely to benefit from fast acting compression than those with poorer cognitive performance. The implication from the mismatch theory is that the more the hearing aid processing causes the signal to differ from the representation stored in the long term memory, the greater the predictive role of cognition will be.…”
supporting
confidence: 93%
“…Lunner (2003) also suggested that it is important to note that the hearing aid processing may in itself be cognitively demanding. This is in agreement with the results reported by Gatehouse et al (2006) and Cox and Xu (2010) who showed that listeners with greater cognitive skills were more likely to benefit from fast acting compression than those with poorer cognitive performance. The implication from the mismatch theory is that the more the hearing aid processing causes the signal to differ from the representation stored in the long term memory, the greater the predictive role of cognition will be.…”
supporting
confidence: 93%
“…In the domain of hearing aids, it has been shown that WMC correlates with aided speech recognition in noise performance (Foo, Rudner, Rönnberg & Lunner, 2007;Gatehouse, Naylor & Elberling, 2003, 2006a, 2006bLunner, 2003, Lunner andSundewall-Thorén, 2007). The ability to derive benefit from digital signal processing algorithms in hearing aids is also associated with WMC (Arehart et al, 2013;Cox & Xu, 2010;Lunner, 2003;Lunner and Sundewall-Thorén, 2007;Rudner, Foo, SundewallThorén, Lunner & Rönnberg, 2008;Rudner, Foo, Lunner & Rönnberg, 2009;.…”
Section: Working Memorymentioning
confidence: 99%
“…Most studies (Cox & Xu, 2010; Foo et al, 2007; Gatehouse, Naylor, & Elberling, 2003; Gatehouse et al, 2006; Lunner & Sundewall-Thoren, 2007; Rudner, Foo, Ronnberg, & Lunner, 2009) used a two-channel wide-dynamic range compressor, as was the standard approach in wearable aids at that time. Results may be different with higher numbers of compression channels, which can produce a variety of complex envelope modifications (Souza, Hoover, Gallun, & Brennan, 2010).…”
mentioning
confidence: 99%